Assessing operational efficiency and the use of strategic capabilities in the rail transport industry in Namibia - Ochurub , Michael; Jeremiah, Andrew (Namibian Journal for Research, Science and Technology, 2022)
This paper assessed the operational efficiency as well as the use of valuable resources and strategic capabilities within the rail transport industry/sector in Namibia, with specific reference to TransNamib Holdings Limited. This paper also focuses on the long-term direction of the rail transport sector as well as the causes of poor performance in the sector. The researchers analysed the questionnaires using descriptive statistics. The researchers explored and presented the individual variables to show specific values, highest and lowest values, trends, propositions and distribution values. The major findings from the data collected revealed that available resources and strategic capabilities are effectively utilized to optimize operational efficiency and that the top management does not pay much attention to development of strategic capabilities, customer value, new strategies, corporate governance, risk management, communication, benchmarking, knowledge management etc. It is also evident from that findings that the main causes of poor performance are the lack of strategic direction and long-term objectives, decline in volumes transported, lack of new technologies to create value, lack of funding or financial assistance from the shareholders, lack of performance agreements and measures as well as the aging and poor rail transport infrastructure. It is recommendable that TransNamib Holdings Limited develop strategies to turn around the current situation to transform the company into self-sustaining and profitable organization. The rail transport sector needs restructuring to streamline the business operations, with more focus on core business, secure funding, enhanced customer services, enhance value proposition for road-to-rail strategy, and enhancing stakeholder and shareholder relations.